COMPARATIVE ANALYSIS OF THE PROFESSIONAL ASPIRATIONS OF LYCEUM STUDENTS (ACCORDING TO THE RESULTS OF THE FINAL EXAMS FOR OBTAINING POLISH AND INTERNATIONAL CERTIFICATES) - Yedzheyak Lena (Borys Grinchenko Kyiv Metropolitan University, 2021)
The secondary school-leaving examination is an important moment in the life of a young person. It is a kind of border after which acquired social skills and educational resources will affect the awakening and embedding of professional aspirations and will allow adults to make decisions on matters of further life path. This path begins in elementary school and counts in the student's life for about twelve years. Therefore, it seems reasonable to assume that after such a period of education and pedagogical interactions, one would expect the student to know his strengths, passions, aspirations, and thus see the shape of his future life path and know how to implement it. It was assumed that with different curriculum curricula, access to knowledge is different, so the impact of these differences on the level of students' professional aspirations was compared to examine the actual state of this phenomenon. At the beginning of the article, terminology and definitions of professional aspirations as well as their levels and conditions in the literature are presented. Then, the results of research carried out in two classes of the same high school, but learning in different core curricula, are presented. Finally, the results were summarized and conclusions were drawn. The study showed that different curricula gave different results of students' knowledge.According to these indicators, the author made a corresponding comparison of the impact of these differences on the level of professional aspirations of students. In addition, the article describes in detail the actual state of the situation. The summarized results of the study on the teaching of classes in different programs made it possible to make suggestions for further educational prospects. The main conclusion is that educational programs for classes with Polish certificates require changes in the orientation of young people to their professional aspirations, in order to plan further educational and professional path.